The effect of green innovation in mediating the effect of ownership on profitability growth - Rahman, Syarif Syahrul; Heniwati, Elok; Helmi, Syarif M. (Journal of Contemporary Accounting, 2025)
This study investigates the Influence of Green Innovation (GI) in mediating the effect of Ownership on profitability growth, based on the Resource-Based View (RBV) theory. Profitability growth is measured using Return on Assets (ROA) for companies listed in the LQ45 index during the 2018–2022 period, with purposive sampling. Data analysis was conducted using Panel Data Regression Analysis through EViews 12 software. The results show that Ownership does not have a direct impact on profitability growth, while GI has a significant influence. Ownership also significantly affects GI; however, GI does not mediate the relationship between Ownership and profitability growth. These findings suggest that although Ownership does not directly drive profitability growth, it promotes GI initiatives that do. Moreover, while GI significantly enhances profitability growth, it does not mediate the indirect effect of Ownership on this growth.